Probiotics for the Management of Pediatric Gastrointestinal Disorders: Position Paper of the ESPGHAN Special Interest Group on Gut Microbiota and Modifications. Issue 2 (11th October 2022) - Szajewska, Hania; Berni Canani, Roberto; Domellöf, Magnus; Guarino, Alfredo; Hojsak, Iva; Indrio, Flavia; Lo Vecchio, Andrea; Mihatsch, Walter A.; Mosca, Alexis; Orel, Rok; Salvatore, Silvia; Shamir, Raanan; et al.
Abstract : Background: Probiotics, defined as live microorganisms that, when administered in adequate amounts, confer a health benefit on the host, are widely used despite uncertainty regarding their efficacy and discordant recommendations about their use. The European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) Special Interest Group on Gut Microbiota and Modifications provides updated recommendations for the use of probiotics for the management of selected pediatric gastrointestinal disorders. Methods: All systematic reviews and/or meta-analyses, as well as subsequently published randomized controlled trials (RCTs) (until December 2021), that compared the use of probiotics in all delivery vehicles and formulations, at any dose, with no probiotic (ie, placebo or no treatment), were eligible for inclusion. The recommendations were formulated only if at least 2 RCTs on a similar well-defined probiotic strain were available. The modified Delphi process was used to establish consensus on the recommendations. Results: Recommendations for the use of specific probiotic strains were made for the management of acute gastroenteritis, prevention of antibiotic-associated diarrhea, nosocomial diarrhea and necrotizing enterocolitis, management of Helicobacter pylori infection, and management of functional abdominal pain disorders and infant colic. Conclusions: Despite evidence to support the use of specific probiotics in some clinical situations, further studies confirming the effect(s) and defining the type, dose, and timing of probiotics are still often required. The use of probiotics with no documented health benefits should be discouraged.